Experimental Investigation of Counter Flow Heat Exchanger with Swirling - Yadav, Omprakash; Kumar Yadav, Vinod; Tiwari, Sumit (International Journal of Engineering and Technology, 2018)
The objective of this experimental work is to investigate and compare the performance of counter flow heat exchanger without and with swirling flow. Heat exchangers are commonly used for heating and cooling of fluids. Heat exchangers are also critical component of thermal power plants and refrigeration systems that control their effectiveness. Generally, the performance of counter flow heat exchanger is better than parallel flow heat exchanger. In this experimental work, it has been tried to improve the performance of counter flow heat exchanger using cold fluid swirling flow arrangement inside the outer tube. The developed experimental set up consists of two concentric tubes. Outer tube is made of mild steel having inner and outer diameters of 32 mm and 36 mm respectively. Inner tube is made of copper with inner and outer diameter as 18 mm and 21 mm respectively. To measure the mass flow rate of hot and cold fluid two calibrated Rotameters were used. To take reading of temperature of hot and cold fluid, four digital thermometers were used. The experimental results revealed that the performance of counter flow heat exchanger with swirling is better than the performance of counter flow heat exchanger without swirling.Â Â Â